POLIMORFISME GEN TRANSFERIN P570S TERHADAP KADAR HEMOGLOBIN (HB) PADA REMAJA PUTRI PONDOK PESANTREN DI YOGYAKARTA - Siti Wahyuningsih; Sri Wahyuni; Arta Farmawati; Ahmad Hamim Sadewa; Zainal Arifin Nang Agus (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Transferrin P570s. Gene Polymorphism Against Hemoglobin (Hb) Levels in Adolescent Girls Islamic Boarding Schools In YogyakartaBackground: Anemia in adolescent girls is one of the nutrients problem. Transferin P570S gene polymorphism has an effect on glycosylated transferin so it can accelerate the degradation transferin. This can cause a decrease in transferrin function and interfere Fe homeostasis. The lack of Fe intake is one cause of the anemia. Objectives: To investigate correlation P570S transferrin gene polymorphisms with iron status as risk factor for iron deficiency anemia in adolescent girls. Methods: Desain of this study was case control. Eighty one adolescent girls living in the boarding school were included in this study. Blood samples used for biochemical examination of the blood and to detect the presence of P570S transferin polymorphism. Genotype frequencies between groups were analyzed using Chi square test and calculated the Odds Ratio (OR). Comparison of the mean rate of hemoglobin between genotype groups were analyzed statistically using One-way ANOVA test. Results: Transferin P570S polymorphism frequency in anemic girls with the CC was 68.4%, CT was 26.3%, TT was 5.3%, C allele frequency= 81.6% and T allele= 18.4%. The odds ratio (OR) P570S transferrin gene polymorphisms for polymorphic genotypes of 0.783 and for the T allele is 0.991. On the subject of anemia with polymorphic genotypes have hemoglobin levels 11.45 while wild type 11.6 (p= 0.000). On the subject of IDA with polymophic genotypes have hemoglobin levels 11.45 while wild type genotype 11.6 (p= 0.190). Conclusion: Genotype frequencies P570S transferring gene polymorphism in adolescent girls at the boarding school who suffer anemia of 31.6% and 35.7% of IDA. The mean hemoglobin levels in subjects with polymorphic genotype lower than the wild type.